2020
DOI: 10.1080/09546553.2020.1785876
|View full text |Cite
|
Sign up to set email alerts
|

Right-Wing Authoritarian and Explicit Prejudice Attitude Responses to the Paris Terror Attacks: A Within-Subjects Analysis

Abstract: When a terror attack occurs people appear to be prepared, in the short term, to be more accepting of authoritarian sanctions against outgroup members, particularly if sanctions are targeted against members of the outgroup perceived as responsible for the attack. The current study examined 42 British participants' scores on measures of Right wing authoritarianism (RWA) and explicit prejudice (EP) before, within 36 hours of, and one year after the November 2015 Paris terror attacks. As higher scores on RWA measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Hudson et al (2019) demonstrated that this empathic deficit for suffering outgroup members is especially pronounced among those who report high levels of prejudice-related personality traits such as social dominance orientation, defined as the extent to which one desires one’s ingroup to dominate and be superior to outgroups (Pratto et al, 1994). In the present study, we extend the sparse prejudice-related personality traits and outgroup empathy deficit research by examining the role of RWA because it has been consistently shown to be associated with greater outgroup-directed prejudice (Duckitt & Sibley, 2007; Gorska et al, 2022; Hodson & Costello, 2007; Sullivan & Hutchings, 2022).…”
Section: Intergroup Empathic Responding and Rwamentioning
confidence: 90%
“…Hudson et al (2019) demonstrated that this empathic deficit for suffering outgroup members is especially pronounced among those who report high levels of prejudice-related personality traits such as social dominance orientation, defined as the extent to which one desires one’s ingroup to dominate and be superior to outgroups (Pratto et al, 1994). In the present study, we extend the sparse prejudice-related personality traits and outgroup empathy deficit research by examining the role of RWA because it has been consistently shown to be associated with greater outgroup-directed prejudice (Duckitt & Sibley, 2007; Gorska et al, 2022; Hodson & Costello, 2007; Sullivan & Hutchings, 2022).…”
Section: Intergroup Empathic Responding and Rwamentioning
confidence: 90%